A robust power allocation algorithm for underwater acoustic cooperative communication network - Xinbin LI; Lingmei ZHANG; Song HAN; Zhipeng HUANG; Zhixin LIU (Dianxin kexue)
In consideration of the issues of the survival time of node, the uncertainness of channel state information and the poor quality of the service in underwater acoustic cooperative communication network, a robust power allocation algorithm was proposed. Firstly, the residual energy of node was considered in the optimization function, and the change of transmitted power was proportional to the remaining energy, thereby balancing the energy consumption and increasing the survival time of the nodes. Secondly, the uncertainty was further introduced into the optimization function to improve the ability of against uncertainty in underwater. At the same time, in order to make sure that the quality of the service, the minimum communication capacity requirements were considered in the optimization function. The simulation results show that the proposed algorithm not only extends the survival time of node, but also improves the performance of system.